ANALISIS YURIDIS PENERAPAN PP NOMOR 47 TAHUN 2012 TENTANG TANGGUNG JAWAB SOSIAL DAN LINGKUNGAN PERSEROAN TERBATAS (STUDI PADA PTPN IV UNIT PASIR MANDOGE) - ABDUL AZIS MANURUNG (PREMISE LAW JURNAL, 2016)
By the issuance of the Government Regulation No. 47/2012 on TJSL (Environmental and Social Responsibility) indicates that the responsibility of implementing Corporate Social Responsibility (CSR) does not only depends on commitment and voluntary moral actions but also on legal responsibility which is mandatory in the Indonesian legal sources like laws and government regulations as their operational manuals. The concept of CSR involves partnership responsibility among the government, Non-Government Organizations (NGOs), and stakeholders. BUMN (State-Owned Enterprises) is one of the government’s important elements in the strategic economic policy of the developing countries. Its existence has the most important influence on The Third World’s development. The existence of PTPN IV is expected to be able to increase the people’s economic quality. Keywords: Environmental, Social, Responsibility